Light signaling controls nuclear architecture reorganization during seedling establishment - Bourbousse, Clara; Mestiri, Imen; Zabulon, Gerald; Bourge, Mickaël; Formiggini, Fabio; Koini, Maria A; Brown, Spencer C; Fransz, Paul; Bowler, Chris; Barneche, Fredy (Proceedings of the National Academy of Sciences - PNAS, 2015)
The spatial organization of chromatin can be subject to extensive remodeling in plant somatic cells in response to developmental and environmental signals. However, the mechanisms controlling these dynamic changes and their functional impact on nuclear activity are poorly understood. Here, we determined that light perception triggers a switch between two different nuclear architectural schemes during Arabidopsis postembryonic development. Whereas progressive nucleus expansion and heterochromatin rearrangements in cotyledon cells are achieved similarly under light and dark conditions during germination, the later steps that lead to mature nuclear phenotypes are intimately associated with the photomorphogenic transition in an organ-specific manner. The light signaling integrators DE-ETIOLATED 1 and CONSTITUTIVE PHOTOMORPHOGENIC 1 maintain heterochromatin in a decondensed state in etiolated cotyledons. In contrast, under light conditions cryptochrome-mediated photoperception releases nuclear expansion and heterochromatin compaction within conspicuous chromocenters. For all tested loci, chromatin condensation during photomorphogenesis does not detectably rely on DNA methylation-based processes. Notwithstanding, the efficiency of transcriptional gene silencing may be impacted during the transition, as based on the reactivation of transposable element-driven reporter genes. Finally, we report that global engagement of RNA polymerase II in transcription is highly increased under light conditions, suggesting that cotyledon photomorphogenesis involves a transition from globally quiescent to more active transcriptional states. Given these findings, we propose that light-triggered changes in nuclear architecture underlie interplays between heterochromatin reorganization and transcriptional reprogramming associated with the establishment of photosynthesis.